A New Method for the Isolation and Purification of Trigonelline as Hydrochloride from Trigonella foenum-graecum L. - Iqbal Hasan AL-Khateeb (مجلة بغداد للعلوم, 2019)
Separation of Trigonelline, the major alkaloid in fenugreek seeds, is difficult because the extract of these seeds usually contains Trigonelline, choline, mucilage, and steroidal saponins, in addition to some other substances. This study amis to isolate the quaternary ammonium alkaloid (Trigonelline) and choline from fenugreek seeds (Trigonella-foenum graecum L.) which have similar physiochemical properties by modifying of the classical method. Seeds were defatted and then extracted with methanol. The presence of alkaloids was detected by using Mayer's and Dragendorff's reagents. In this work, trigonilline was isolated with traces of choline by subsequent processes of purification using analytical and preparative TLC techniques. Further identification was done by using HPLC, IR and MP. Pure Trigonelline was isolated from the seeds of Trigonella-foenum graecum excluding other alkaloid like choline. In this study, a new, fast and convenient method for isolation and purification of Trigonelline from fenugreek seeds has been established. Unlike other methods, this one excludes all the non-alkaloidal components from the fenugreek seeds extract.